Industry 4.0 in commercial airlines: a bibliometric analysis - Omido, Nicholas; Luke, Rose; Mageto, Joash; Ombati, Thomas (Frontiers in Future Transportation, 2025)
Commercial airlines face numerous challenges related to operational inefficiencies, poor maintenance practices, overcrowding of airports, supply chain complexity, lack of seamless customer experience, safety issues, data privacy and security issues, increasing fuel prices, and sustainability issues; however, Industry 4.0 technologies are widely regarded as a transformative solution, offering advanced tools and methodologies to address these challenges effectively. Despite the potential benefits of Industry 4.0 technologies, there remains a lack of comprehensive understanding regarding their extent and impact on commercial airlines. The study examined the current state of research on Industry 4.0 in commercial airlines, identified the most significant research topics within this domain, and proposed a future research agenda. The bibliometric analysis was based on 5,113 documents extracted from the Scopus and Web of Science databases, covering 2,109 journals, with an annual publication growth rate of 9.34%. However, Africa’s contribution remains minimal, accounting for less than 1% of the total research output analyzed, highlighting a significant research gap on the continent. The contemporary literature has focused on artificial intelligence, automation, big data analytics, the Internet of Things, and integrating Industry 4.0 technologies. The study was also used to identify the future research agenda of Industry 4.0 in commercial airlines, which includes human-centric approaches, integration of advanced technologies, cybersecurity, environmental sustainability, and ethical and legal implications.